2012
DOI: 10.6002/ect.2012.0026
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant-Related Hip Pain After Orthotopic Liver Transplant

Abstract: Objectives: Immunosuppressant-related hip pain can greatly affect a patient's mobility and increase the number of total hip arthroplasties. We investigated risk factors and causes of hip pain after orthotopic liver transplant. Materials and Methods:The medical records of 175 adult orthotopic liver transplant patients, who were followed-up for more than 2 years, were retrospectively reviewed. Data collected from the records included primary disease, medications, biochemical results, Child-Turcotte-Pugh score, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This wide variation was likely due to differences in surveillance methodology and patient type. For example, the osteoporosis incidence in a study with sporadic surveillance [13] was only 1.1%, whereas a study with regular surveillance by Bjoro et al reported 65.1% [8]. In the case of patient type, patients with cholestatic liver disease were reported to have poorer BMD than patients with non-cholestatic liver disease [8].…”
Section: Discussionmentioning
confidence: 94%
“…This wide variation was likely due to differences in surveillance methodology and patient type. For example, the osteoporosis incidence in a study with sporadic surveillance [13] was only 1.1%, whereas a study with regular surveillance by Bjoro et al reported 65.1% [8]. In the case of patient type, patients with cholestatic liver disease were reported to have poorer BMD than patients with non-cholestatic liver disease [8].…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, all previous case reports, and reviews of CIPS in patients who have undergone renal transplantation involved bones around the knees or feet [ [12] , [13] , [14] ]. However, Li et al reported the incidence of CIPS in 4 out of 11 patients presenting with hip pain following liver transplantation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that less than 4% patients of AVN patients who underwent renal transplantation, 6.3% patients of AVN patients following cardiac transplantation, and 2% of patients following liver transplantation exhibit osteonecrosis of the hip (Hedri et al, 2007;Lieberman, Roth, Elsissy, Dorey, & Kobashigawa, 2008;Schmitt-Sody et al, 2008). The most commonly reported organ transplantation-induced AVN is caused by long-term administration of corticosteroid therapy (Li et al, 2013). However, the present study described a case in which AVN was induced following high-dosage and short-term systemic cor- The case presented here is the second case to develop bilateral AVN after hand transplantation.…”
Section: Discussionmentioning
confidence: 99%